Magnetoelectric properties of la-modified BiFeO3 thin films on strontium ruthenate (SrRuO3) buffered layer - Deus, Regina C. [UNESP]; Foschini, César R. [UNESP]; Varela, José A. [UNESP]; Longo, Elson [UNESP]; Simões, Alexandre Z. [UNESP] (My University, 2014)
This paper focus on the magnetoelectric coupling (ME) at room temperature in lanthanum modified bismuth ferrite thin film (BLFO) deposited on SrRuO 3-buffered Pt/TiO2/SiO2/Si (100) substrates by the soft chemical method. BLFO film was coherently grown at a temperature of 500°C. The magnetoelectric coefficient measurement was performed to evidence magnetoelectric coupling behavior. Room temperature magnetic coercive field indicates that the film is magnetically soft. The maximum magnetoelectric coefficient in the longitudinal direction was close to 12 V/cmOe. Dielectric permittivity and dielectric loss demonstrated only slight dispersion with frequency due the less two-dimensional stress in the plane of the film. The spontaneous polarization of the film was 25 μC/cm2. The film has a piezoelectric coefficient, d33, equal to 85 pm/V and a weak pulse width dependence indicating intrinsic ferroelectricity. Retention measurement showed no decay of polarization while piezoelectric response was greatly improved by the conductor electrode. Polarization reversal was investigated by applying dc voltage through a conductive tip during the area scanning. We observed that various types of domain behavior such as 71° and 180° domain switchings, and pinned domain formation occurred.